A tale of four practices: A comparative analysis of high and low performing patient-centered medical homes. Issue 6 (18th September 2017) - Miller-Day, Michelle; Applequist, Janelle; Zabokrtsky, Keri; Dalton, Alexandra; Kellom, Katherine; Gabbay, Robert; Cronholm, Peter F.
Abstract : Purpose: The Patient-Centered Medical Home (PCMH) has become a dominant model of primary care re-design. This transformation presents a challenge to many care delivery organizations. The purpose of this paper is to describe attributes shaping successful and unsuccessful practice transformation within four medical practice groups. Design/methodology/approach: As part of a larger study of 25 practices transitioning into a PCMH, the current study focused on diabetes care and identified high- and low-improvement medical practices in terms of quantitative patient measures of glycosylated hemoglobin and qualitative assessments of practice performance. A subset of the top two high-improvement and bottom two low-improvement practices were identified as comparison groups. Semi-structured interviews were conducted with diverse personnel at these practices to investigate their experiences with practice transformation and data were analyzed using analytic induction. Findings: Results show a variety of key attributes facilitating more successful PCMH transformation, such as empanelment, shared goals and regular meetings, and a clear understanding of PCMH transformation purposes, goals, and benefits, providing care/case management services, and facilitating patient reminders. Several barriers also exist to successful transformation, such as low levels of resources to handle financial expense, lack of understanding PCMH transformation purposes, goals, and benefits, inadequate training and management of technology, and low team cohesion. Originality/value: Few studies qualitatively compare and contrast high and low performing practices to illuminate the experience of practice transformation. These findings highlight the experience of organizational members and their challenges in practice transformation while providing quality diabetes care.